Resin composition for optical semiconductor encapsulation, resin molding for optical semiconductor encapsulation, optical semiconductor encapsulation material and optical semiconductor device

JP2025025338APending Publication Date: 2025-02-21NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023130018
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0017】 本発明の光半導体封止用樹脂組成物は、バイオ比率が10質量%以上であるため、環境に配慮できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025338000001
    Figure 2025025338000001
  • Figure 2025025338000002
    Figure 2025025338000002
  • Figure 2025025338000003
    Figure 2025025338000003
Patent Text Reader

Abstract

To provide environmentally friendly resin compositions for optical semiconductor encapsulation, and resin moldings for optical semiconductor encapsulation, optical semiconductor encapsulation materials, and optical semiconductor devices using the same.SOLUTION: The bio ratio of a resin composition for optical semiconductor encapsulation is 10 mass% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical semiconductor encapsulating resin composition, an optical semiconductor encapsulating resin molded product, an optical semiconductor encapsulant, and an optical semiconductor device. [Background technology]

[0002] Optical semiconductor elements are sealed and assembled into devices using ceramic or plastic packages. Since ceramic packages are made of relatively expensive materials and are poorly suited for mass production, plastic packages are predominant. Among these, the technology of transfer molding an epoxy resin composition that has been previously compressed into tablets has become mainstream in terms of workability, mass production, and reliability.

[0003] Conventional resin compositions for sealing optical semiconductors are composed of petroleum-derived materials (eg, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2021-528503 Summary of the Invention [Problem to be solved by the invention]

[0005] Conventional resin compositions for sealing optical semiconductors are composed of petroleum-derived materials, and there is room for improvement in terms of the depletion of petroleum resources and CO2 emissions. The present invention is devised to solve the above-mentioned problems newly discovered by the present inventors, and has an object to provide an environmentally friendly resin composition for encapsulating an optical semiconductor, as well as a resin molded product for encapsulating an optical semiconductor, an optical semiconductor encapsulant, and an optical semiconductor device each using the same. [Means for solving the problem]

[0006] The present invention (1) relates to a resin composition for sealing an optical semiconductor, having a bio ratio of 10 mass % or more.

[0007] The present invention (2) relates to the resin composition for encapsulating optical semiconductors according to the present invention (1), which contains a plant-derived diol.

[0008] The present invention (3) relates to the resin composition for encapsulating an optical semiconductor according to the present invention (2), wherein the diol is a diol having hydroxy groups at both ends of the main chain.

[0009] The present invention (4) relates to the resin composition for encapsulating an optical semiconductor according to the present invention (2) or (3), wherein the diol is a polymer.

[0010] The present invention (5) relates to the resin composition for encapsulating an optical semiconductor according to any one of the present inventions (1) to (4), which has an in-line transmittance at a wavelength of 400 nm of 50% or more when cured (in a cylindrical shape with a diameter of 50 mm and a thickness of 1 mm) by the following method: (Method of producing hardened body) The resin composition is transferred into a mold heated to 150±5°C under pressure using a transfer molding machine, and the resin is extruded by transfer molding into a mold that has been molten by heating, and cured for 4 minutes without any voids to obtain a uniform cured product. The product is then removed from the mold and heated in a dryer at 150°C for 3 hours to completely cure, obtaining a cured product.

[0011] The present invention (6) relates to the resin composition for encapsulating optical semiconductors according to any one of the present inventions (1) to (5), which has an in-line transmittance of 50% or more at a wavelength of 400 nm after performing solder reflow three times at 265° C. on a cured product (cylinder-shaped with a diameter of 50 mm and a thickness of 1 mm) obtained by the above method.

[0012] The present invention (7) relates to the resin composition for encapsulating optical semiconductors according to any one of the present inventions (1) to (6), wherein the glass transition temperature of the cured product (cylindrical shape with a diameter of 50 mm and a thickness of 1 mm) obtained by the above method is 0° C. or higher.

[0013] The present invention (8) relates to the optical semiconductor encapsulating resin composition according to any one of the present inventions (1) to (7), which is used for transfer molding.

[0014] The present invention (9) relates to an optical semiconductor encapsulating resin molded product, which contains the optical semiconductor encapsulating resin composition according to any one of the present inventions (1) to (8).

[0015] The present invention (10) relates to an optical semiconductor encapsulant obtained by molding the optical semiconductor encapsulating resin molded product according to the present invention (9).

[0016] The present invention (11) relates to an optical semiconductor device comprising an optical semiconductor element and the optical semiconductor encapsulant according to the present invention (10) for encapsulating the optical semiconductor element. Effect of the Invention

[0017] The optical semiconductor encapsulating resin composition of the present invention has a bio-ratio of 10% by mass or more, and is therefore environmentally friendly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The optical semiconductor encapsulating resin composition of the present invention has a bio-ratio of 10% by mass or more, which is environmentally friendly, prevents the depletion of petroleum resources, and reduces CO2 emissions.

[0019] In this specification, the bio-ratio means the content of carbon derived from living organisms. Biological carbon contains a certain percentage of radioactive isotopes (C-14), whereas petroleum-derived carbon contains almost no C-14. Therefore, the bio-ratio can be calculated by measuring the concentration of C-14 contained in the measurement target. In this specification, the bio-ratio is measured in accordance with ASTM D6866-22, a standard used in the bioplastics industry.

[0020] In this specification, when a numerical range is indicated by the symbol "-", such as 50 to 100% by mass, the upper and lower limits are included. For example, 50 to 100% by mass means 50% by mass or more and 100% by mass or less.

[0021] <Optical semiconductor encapsulation resin composition> The resin composition for sealing optical semiconductors of the present invention has a bio ratio (content of carbon derived from living organisms) of 10% by mass or more, preferably 10 to 50% by mass, more preferably 10 to 30% by mass, and even more preferably 10 to 20% by mass. The higher the bio ratio, the more the environmental load can be reduced, so the upper limit of the bio ratio is not particularly limited. However, at present, only limited raw materials such as diols are biologically derived from the raw materials used in the resin composition for sealing optical semiconductors, so the above upper limit is preferable. If the bio ratio exceeds 50% by mass, the progress of the thermal reaction is inhibited, making it difficult to adjust the reactivity, which may lead to a decrease in pulverization and tableting properties. In addition, there is a possibility that the problem of uncured products may occur.

[0022] The resin composition for sealing optical semiconductors having a bio ratio within the above range can be achieved by using a raw material derived from a living organism, for example, a diol derived from a living organism, preferably a diol derived from a plant. It can also be achieved by using a raw material having an isosorbide structure, which will be described later. These can be used alone or in combination of two or more kinds.

[0023] The diol and the raw material having an isosorbide structure are preferably diols having hydroxy groups at both ends of the main chain, which tends to adjust the glass transition temperature and further improve the light transmittance and heat resistance.

[0024] The diol and the raw material having an isosorbide structure are preferably polymers, more preferably polymers having hydroxy groups at both ends of the main chain, which tends to adjust the glass transition temperature and further improve the light transmittance and heat resistance.

[0025] <<Diols derived from living organisms>> In the section <<Biological Diols>>, a specific example of a biological diol will be described, but in this section, biological diols other than raw materials having an isosorbide structure, which will be described later, will be described.

[0026] Examples of biologically derived diols include polytetramethylene ether glycol (PTMG). These can be used alone or in combination of two or more. Among them, polytetramethylene ether glycol is preferred. Biologically derived polytetramethylene ether glycol is synthesized by ring-opening tetrahydrofuran derived from plants.

[0027] Polytetramethylene ether glycol is a polymer represented by the following formula (B) and is a diol having hydroxy groups at both ends of the molecular chain. [ka] (In formula (B), m is the number of repeating units.)

[0028] The number average molecular weight of the biologically derived diol such as polytetramethylene ether glycol is preferably 100 to 5000, more preferably 500 to 2000, and further preferably 600 to 900. This tends to further improve light transmittance and heat resistance. In this specification, the number average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated as polystyrene equivalent.

[0029] The hydroxyl value of the biologically derived diol such as polytetramethylene ether glycol is preferably 50 to 300 mgKOH / g, more preferably 100 to 250 mgKOH / g, and further preferably 130 to 200 mgKOH / g, which tends to further improve light transmittance and heat resistance. In this specification, the hydroxyl value refers to the hydroxyl value described in JIS K 0070:1992, and is the number of milligrams of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of a sample is acetylated.

[0030] In 100% by mass of the optical semiconductor encapsulating resin composition, the proportion of the biologically derived diol such as polytetramethylene ether glycol (excluding raw materials having an isosorbide structure) is preferably 5 to 90% by mass, more preferably 5 to 21% by mass, and even more preferably 5 to 15% by mass, which tends to further improve the light transmittance, heat resistance, crushability, and tablet moldability.

[0031] <<Raw materials containing isosorbide structure>> A raw material having an isosorbide structure will be described. In this specification, the isosorbide structure means a structure derived from isosorbide (a compound represented by the following formula (1-1)), specifically a structure represented by the following formula (1-2). Therefore, the raw material having an isosorbide structure only needs to have a structure represented by the following formula (1-2), and in addition to the compound represented by the following formula (1-1), it also includes, for example, a compound having a structural unit derived from isosorbide (a unit represented by the following formula (1-3) (* in the following formula (1-3) is a bond)). [ka] [ka] [ka]

[0032] The isosorbide structure of the raw material having an isosorbide structure is preferably a structure derived from isosorbide derived from a living organism, and more preferably a structure derived from isosorbide derived from a plant. By using a raw material using a biomass material such as a material derived from a living organism as the raw material having an isosorbide structure, the environmental load can be reduced.

[0033] The raw material having an isosorbide structure is not particularly limited as long as it has an isosorbide structure. Specific examples of raw materials having an isosorbide structure include, for example, isosorbide; a polymer having a structural unit derived from isosorbide; isosorbide having an epoxy group; an isosorbide derivative in which a substituent is added to isosorbide such as isosorbide having a hydroxyl group; isosorbide glycidyl ether, etc. These can be used alone or in combination of two or more kinds. Among them, a polymer having a structural unit derived from isosorbide and an isosorbide derivative are preferred, and a polymer having a structural unit derived from isosorbide is more preferred. In addition, as the isosorbide derivative, isosorbide having an epoxy group is preferred.

[0034] The raw material having an isosorbide structure is preferably a polyhydric alcohol, which tends to adjust the glass transition temperature and further improve light transmittance and heat resistance. The polyhydric alcohol may be a compound having two or more hydroxyl groups, but is preferably a diol (glycol). That is, the raw material having an isosorbide structure is preferably a compound having two or more hydroxyl groups, and more preferably a diol (glycol). When the isosorbide structure of the raw material having an isosorbide structure is a structure derived from biological isosorbide, and the raw material having an isosorbide structure is a diol, it corresponds to a biological diol.

[0035] Examples of polymers having a structural unit derived from isosorbide include homopolymers (isosorbide homopolymers) whose structural units are all derived from isosorbide, and copolymers (isosorbide copolymers) having structural units derived from isosorbide and other structural units. These can be used alone or in combination of two or more. When an isosorbide homopolymer is used, compatibility with other compounding agents can be improved, but the molecular weight of the cured product may not be sufficiently large. On the other hand, when an isosorbide copolymer is used, compatibility with other compounding agents is improved, and the molecular weight of the cured product tends to be sufficiently large. Therefore, isosorbide copolymers are preferred as polymers having structural units derived from isosorbide. The copolymer may be a block polymer or a random polymer.

[0036] Other structural units (structural units other than those derived from isosorbide) contained in the isosorbide copolymer include, for example, structural units derived from alkanediol. These can be used alone or in combination of two or more. Among them, structural units derived from alkanediol are preferred. That is, as a polymer having a structural unit derived from isosorbide, a polymer having a structural unit derived from isosorbide and a structural unit derived from alkanediol is preferred, and a polymer having a structural unit derived from isosorbide and a structural unit derived from alkanediol and having hydroxyl groups at both ends is more preferred.

[0037] The polymer having a constitutional unit derived from isosorbide and a constitutional unit derived from an alkanediol is not particularly limited as long as it is a polymer having both constitutional units, but a polymer represented by the following formula (A) is preferred. The polymer represented by the following formula (A) is a diol having hydroxy groups at both ends of the molecular chain. [ka] (In formula (A), the multiple R's are structural units derived from isosorbide or structural units derived from an alkanediol, and the polymer has at least one of both structural units. n is the number of repeating units.)

[0038] A specific example of a structural unit derived from isosorbide is a unit represented by the following formula (1-3) (in the following formula (1-3), * represents a bond), and a specific example of a structural unit derived from an alkanediol is a divalent alkylene group formed by the alkane of the alkanediol. [ka]

[0039] An alkanediol is a polyhydric alcohol having two hydroxyl groups. The alkanediol can be used alone or in combination of two or more kinds. The position of the hydroxyl group of the alkane is not particularly limited, but it is preferable that at least one hydroxyl group is located at the end of the main chain of the alkane chain, and it is more preferable that both hydroxyl groups are located at the end of the main chain of the alkane chain (the main chain of the alkane chain has hydroxyl groups at both ends). For example, 1,6-hexanediol and 3-methyl-1,5-pentanediol are diols having hydroxyl groups at both ends of the main chain of the alkane chain, and 1,2-hexanediol is a diol having a hydroxyl group at one end of the main chain of the alkane chain.

[0040] The number of carbon atoms in the alkanediol is preferably 1 to 10, more preferably 2 to 9, and even more preferably 3 to 7. This tends to further improve light transmittance and heat resistance.

[0041] Examples of the alkane of the alkanediol include normal alkanes such as n-propane, n-butane, n-pentane, n-hexane, n-heptane, and n-octane; isoalkanes such as isobutane, isopentane, 2-methylpentane, 2-methylhexane, and 2,2,4-trimethylpentane; and the like. These can be used alone or in combination of two or more. Among them, normal alkanes are preferred, and n-propane, n-butane, n-pentane, n-hexane, and n-heptane are more preferred.

[0042] The alkanediol is preferably a diol having hydroxy groups at both ends of the main chain of a normal alkane chain, more preferably 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, or 1,7-heptanediol, and still more preferably 1,4-butanediol, 1,5-pentanediol, or 1,6-hexanediol.

[0043] As described above, the structural unit derived from an alkanediol is a divalent alkylene group formed by the alkane of the alkanediol, and therefore, a person skilled in the art can interpret the above-mentioned preferred embodiments of the alkanediol as preferred embodiments of the alkylene group.

[0044] In the polymer having a structural unit derived from isosorbide and a structural unit derived from an alkanediol, the proportion of the structural unit derived from isosorbide is preferably 20 to 70% by mass, more preferably 35 to 55% by mass, based on 100% by mass of the polymer, which tends to further improve light transmittance and heat resistance.

[0045] In the polymer having a structural unit derived from isosorbide and a structural unit derived from an alkanediol, the proportion of the structural unit derived from an alkanediol is preferably 30 to 80% by mass, more preferably 45 to 65% by mass, based on 100% by mass of the polymer, which tends to further improve light transmittance and heat resistance.

[0046] In the polymer having a constitutional unit derived from isosorbide and a constitutional unit derived from an alkanediol, the total proportion of the constitutional unit derived from isosorbide and the constitutional unit derived from an alkanediol is preferably 98% by mass or more, and may be 100% by mass, in 100% by mass of the polymer. This tends to further improve light transmittance and heat resistance.

[0047] In this specification, the proportion of each structural unit in a polymer is measured by nuclear magnetic resonance spectroscopy (NMR).

[0048] A polymer having a structural unit derived from isosorbide and a structural unit derived from an alkanediol (e.g., a polymer represented by the above formula (A)) can be produced, for example, by reacting isosorbide and an alkanediol in the presence of phosgene to form a carbonate group (-O-(C=O)-O-).

[0049] Examples of isosorbide having an epoxy group include compounds in which the hydroxy group of isosorbide is substituted with a glycidyl ether group (compounds represented by the following formula (1-4)). These can be used alone or in combination of two or more. Among them, compounds in which the hydroxy group of isosorbide is substituted with a glycidyl ether group (compounds represented by the following formula (1-4)) are preferred. In addition, isosorbide having an epoxy group also functions as a thermosetting resin described later, but in the present invention, isosorbide having an epoxy group is treated as a raw material having an isosorbide structure. Thus, in the present invention, as long as it has an isosorbide structure, it is treated as a raw material having an isosorbide structure. [ka]

[0050] Isosorbide having an epoxy group can be produced, for example, by reacting isosorbide with an epihalohydrin such as epichlorohydrin.

[0051] The number average molecular weight of the raw material having an isosorbide structure is preferably 100 to 5000, more preferably 500 to 2000, and further preferably 700 to 1300. This tends to further improve light transmittance and heat resistance. In this specification, the number average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated as polystyrene equivalent.

[0052] The hydroxyl value of the raw material having an isosorbide structure is preferably 50 to 300 mgKOH / g, more preferably 100 to 200 mgKOH / g, and further preferably 130 to 160 mgKOH / g, which tends to further improve light transmittance and heat resistance. In this specification, the hydroxyl value refers to the hydroxyl value described in JIS K 0070:1992, and is the number of milligrams of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of a sample is acetylated.

[0053] The raw material having an isosorbide structure preferably has a content of biologically derived carbon (bio-ratio) of 20% by mass or more, more preferably 40% by mass or more. Since a higher bio-ratio can reduce the environmental load, there is no particular upper limit.

[0054] In 100% by mass of the optical semiconductor encapsulating resin composition, the ratio of the raw material having an isosorbide structure is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, and further preferably 25 to 35% by mass, which tends to further improve the light transmittance and heat resistance.

[0055] <<Thermosetting resin>> As the thermosetting resin (excluding raw materials having an isosorbide structure), epoxy resins can be suitably used. As the epoxy resin, those with little coloring are preferred, and examples thereof include bisphenol A type epoxy resins, bisphenol F type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins, triglycidyl isocyanurate, heterocyclic epoxy resins such as hydantoin epoxy, water-added bisphenol A type epoxy resins, aliphatic epoxy resins, glycidyl ether type epoxy resins, cresol novolac type epoxy resins, etc. These can be used alone or in combination of two or more. Among them, bisphenol A type epoxy resins, alicyclic epoxy resins, and triglycidyl isocyanurate are preferred, and alicyclic epoxy resins are more preferred. In addition, the combined use of bisphenol A type epoxy resins and alicyclic epoxy resins is also preferred. In addition, epoxy resins without aromatic rings are also preferred, and alicyclic epoxy resins and triglycidyl isocyanurate are also more preferred.

[0056] In this specification, alicyclic (alicyclic structure) means a saturated or unsaturated carbon ring structure having no aromaticity (preferably a carbon ring having no unsaturated bond in the ring).

[0057] In 100% by mass of the epoxy resin, the proportion of the bisphenol A type epoxy resin is preferably 10 to 50% by mass, more preferably 20 to 40% by mass, which makes it possible to control the reactivity and adjust the gelation time.

[0058] In 100% by mass of the epoxy resin, the proportion of the epoxy resin having no aromatic ring (preferably the total proportion of the alicyclic epoxy resin and triglycidyl isocyanurate, more preferably the proportion of the alicyclic epoxy resin) is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and may be 100% by mass, thereby obtaining better light transmittance and heat resistance.

[0059] In 100% by mass of the optical semiconductor encapsulating resin composition, the bisphenol A type epoxy resin is preferably 5 to 50% by mass, more preferably 3 to 30% by mass, and further preferably 10 to 20% by mass, which allows the reactivity to be controlled and the gelation time to be adjusted.

[0060] In 100% by mass of the optical semiconductor encapsulating resin composition, the ratio of the epoxy resin having no aromatic ring (preferably the total ratio of the alicyclic epoxy resin and triglycidyl isocyanurate, more preferably the ratio of the alicyclic epoxy resin) is preferably 5 to 60% by mass, more preferably 15 to 50% by mass, and even more preferably 25 to 40% by mass, which provides better light transmittance and heat resistance.

[0061] The optical semiconductor encapsulating resin composition of the present invention may contain a thermosetting resin other than the epoxy resin.

[0062] In 100% by mass of the thermosetting resin, the proportion of the epoxy resin is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, particularly preferably 60% by mass or more, most preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.

[0063] <<Hardening agent>> The curing agent is not particularly limited, but an acid anhydride that causes little coloring in the cured resin composition during or after curing is preferred. Examples of the acid anhydride include aromatic polycarboxylic anhydrides such as phthalic anhydride, trimellitic anhydride, and pyromellitic anhydride; chain polycarboxylic anhydrides such as maleic anhydride; alicyclic polycarboxylic anhydrides such as hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, methylnadic anhydride, nadic anhydride, glutaric anhydride, methyltetrahydrophthalic anhydride, dimethyltetrahydrophthalic anhydride, norbornene dicarboxylic anhydride, methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, methylbicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, and cyclopentane tetracarboxylic anhydride. Among these, alicyclic polyvalent carboxylic acid anhydrides are preferred, with hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and tetrahydrophthalic anhydride being more preferred, and hexahydrophthalic anhydride being even more preferred. In this specification, the alicyclic polycarboxylic acid anhydride means a compound having a carboxylic acid anhydride group and an alicyclic structure. The curing agents can be used alone or in combination of two or more kinds.

[0064] Other curing agents include amine-based curing agents such as metaphenylenediamine, dimethyldiphenylmethane, diaminodiphenylsulfone, m-xylenediamine, tetraethylenepentamine, diethylamine, and propylamine, phenolic resin-based curing agents, and alicyclic polycarboxylic acids such as cyclohexene dicarboxylic acid, cyclopropane dicarboxylic acid, cyclopropane tricarboxylic acid, cyclobutane dicarboxylic acid, cyclohexane tetracarboxylic acid, and cyclooctane dicarboxylic acid. These may also be used alone or in combination of two or more. Among them, alicyclic polycarboxylic acids are preferred, and cyclohexene dicarboxylic acid is more preferred. In this specification, the alicyclic polycarboxylic acid means a compound having an alicyclic structure and a plurality of carboxy groups.

[0065] The amount of the curing agent is not particularly limited, but is preferably 20 to 200 parts by mass, more preferably 60 to 145 parts by mass, relative to 100 parts by mass of the thermosetting resin (preferably epoxy resin). If it is less than 20 parts by mass, the curing speed will be slow, and if it exceeds 200 parts by mass, there is an excess amount relative to the curing reaction, which may cause a decrease in various physical properties. The proportion of the alicyclic polyvalent carboxylic acid anhydride in 100% by mass of the curing agent is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may be 100% by mass. This tends to further improve light transmittance and heat resistance.

[0066] <<Antioxidants>> The optical semiconductor encapsulating resin composition of the present invention may contain an antioxidant, which tends to provide better heat resistance. The antioxidants can be used alone or in combination of two or more kinds. Examples of the antioxidant include phenol-based antioxidants such as 2,6-di-tert-butyl-p-hydrotoluene, 2,6-di-tert-butyl-p-cresol, and 2,6-di-tert-butyl-4-ethylphenol, phosphorus-based antioxidants such as tris(2,4-di-tert-butylphenyl)phosphite, triphenylphosphite, diphenylisodecylphosphite, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and amino-based antioxidants such as diphenylamine, etc. Among these, phenol-based antioxidants and phosphorus-based antioxidants are preferred.

[0067] The amount of the antioxidant to be added is preferably 0.5 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, further preferably 0.5 to 5 parts by mass, and particularly preferably 0.5 to 3 parts by mass, based on 100 parts by mass of the epoxy resin. If the amount is less than 0.5 parts by mass, the heat resistance may decrease, whereas if the amount exceeds 20 parts by mass, the transmittance may decrease.

[0068] <<Curing accelerator>> The optical semiconductor encapsulating resin composition of the present invention preferably contains a curing accelerator, which tends to increase the curing speed and the degree of curing. The curing accelerators can be used alone or in combination of two or more kinds.

[0069] Examples of the curing accelerator include tertiary amines such as triethanolamine and dimethylbenzylamine; imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-methyl-4-methylimidazole; organic phosphorus compounds such as tributyl(methyl)phosphonium dimethylphosphate, tetraphenylphosphonium tetraphenylborate, and triphenylphosphine; diazabicycloalkene compounds such as 1,8-diazabicyclo[5,4,0]undecene-7 and 1,5-diazabicyclo[4,3,0]nonene-5; etc. Among them, tertiary amines are preferred, and dimethylbenzylamine is more preferred.

[0070] The amount of the curing accelerator is not particularly limited, but can be appropriately selected from the range of, for example, 0.1 to 5 parts by mass relative to 100 parts by mass of the epoxy resin, and is preferably 0.1 to 3 parts by mass, and more preferably 0.1 to 2 parts by mass. If the amount of the curing accelerator is too small, the curing speed will be slow and the productivity will decrease, while if the amount of the curing accelerator is too large, the curing reaction will be fast, making it difficult to control the reaction state, and there is a risk of causing reaction variation.

[0071] <<Silane coupling agents>> The optical semiconductor encapsulating resin composition of the present invention preferably contains a silane coupling agent, which can improve the adhesion to a substrate or a lead frame.

[0072] Examples of silane coupling agents include 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethylethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropyltrimethoxysilane. These can be used alone or in combination of two or more. Among them, mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane are preferred, and 3-mercaptopropyltrimethoxysilane is more preferred.

[0073] The amount of the silane coupling agent is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 10 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the epoxy resin, which allows for good and strong adhesion to the substrate or lead frame.

[0074] <<Other additives>> In addition to the above-mentioned components, the resin composition for sealing optical semiconductors of the present invention may contain additives such as a lubricant, a phosphor that changes the wavelength of light, and an inorganic or organic filler that diffuses light, if necessary. These additives may be used alone or in combination of two or more kinds.

[0075] Examples of the lubricant include waxes such as stearic acid, magnesium stearate, and calcium stearate, and talc, etc. When the lubricant is added, the amount of the lubricant added is appropriately set according to the tableting conditions, and is preferably set to, for example, 0.1 to 0.4% by mass of the entire resin composition.

[0076] Examples of phosphors that change the wavelength of light and inorganic / organic fillers that diffuse light include quartz glass powder, talc, silica powder such as fused silica powder and crystalline silica powder, alumina, silicon nitride, aluminum nitride, silicon carbide, and carbon black. These can be used alone or in combination of two or more. When phosphors or inorganic / organic fillers are mixed, their mixing amounts are appropriately set according to molding conditions. Specifically, in the case of phosphors, the mixing amount of the phosphor can be appropriately set within the range of 1% by mass to 60% by mass of the entire resin composition. On the other hand, in the case of fillers (organic / inorganic) that scatter light, the light scattering filler can be appropriately set within the range of 0.5% by mass to 25% by mass of the entire resin molded product.

[0077] <<Reactants>> The optical semiconductor encapsulating resin composition of the present invention may contain reaction products of each compounding ingredient, such as a reaction product of a thermosetting resin with a curing agent.

[0078] <Method of producing optical semiconductor encapsulating resin composition> The method for producing the optical semiconductor encapsulating resin composition of the present invention is not particularly limited as long as it is a method capable of kneading and dispersing the above-mentioned components, but it is preferable to heat treat the composition to give a B-stage state (semi-cured state).

[0079] The method for producing the optical semiconductor encapsulating resin composition of the present invention can be, for example, a production method including a step of kneading a thermosetting resin, a raw material of biological origin, a curing agent, and a curing accelerator to obtain a curable resin composition, and a step of heat-treating the curable resin composition.

[0080] The kneading method is not particularly limited, but may be, for example, a method using an extruder. The kneading temperature is also not particularly limited, and may be appropriately changed depending on the characteristics of the thermosetting resin. It is also possible to set the temperature high so as to advance the reaction during kneading. Specifically, the temperature is preferably 80 to 150°C, more preferably 110 to 130°C.

[0081] The shape of the curable resin composition obtained by kneading is not particularly limited, and examples of the shape include a film, a sheet, particles, and a block.

[0082] The thickness of the curable resin composition obtained by kneading is not particularly limited, but is preferably 1 to 30 mm, more preferably 2 to 20 mm, and even more preferably 2 to 10 mm. If the thickness is less than 1 mm, the composition is thin and easily affected by moisture absorption, whereas if the thickness exceeds 30 mm, it takes a long time to cool and the reaction tends to vary due to internal heat accumulation.

[0083] The curable resin composition obtained by kneading is heat-treated to obtain a B-stage (semi-cured) optical semiconductor encapsulating resin composition. The heat treatment temperature is not particularly limited, but is preferably 25 to 100°C, and more preferably 60 to 80°C. If the temperature is less than 25°C, the curing reaction tends to be slow and the productivity tends to decrease, and if the temperature exceeds 100°C, the curing reaction tends to be fast and it tends to be difficult to terminate the reaction at a predetermined reaction state. The heat treatment time is not particularly limited, and can be appropriately changed depending on the characteristics of the thermosetting resin.

[0084] The optical semiconductor encapsulating resin composition in a B-stage state (semi-cured state) obtained by the heat treatment is preferably subjected to the following steps. A process of crushing and / or granulating the heat-treated curable resin composition (B-stage (semi-cured) optical semiconductor encapsulation resin composition) to obtain a granular curable resin composition.

[0085] In the case of pulverization, the heat-treated resin composition is pulverized to obtain a granular resin composition. The pulverization may be performed using a ball mill, a turbo mill, a hammer mill, a cutter mill, or the like.

[0086] In the case of granulation, the heat-treated resin composition is granulated to obtain a granular resin composition. Before granulation, the resin composition may be pulverized using a ball mill, a turbo mill, etc. The granulation method is not particularly limited, and may include a method using a dry compression granulator.

[0087] The average particle size of the granules obtained by pulverization and / or granulation is not particularly limited, but is preferably 1 to 5000 μm, more preferably 100 to 2000 μm. If it exceeds 5000 μm, the compressibility tends to decrease.

[0088] The step of obtaining the granular curable resin composition is preferably a step of granulating a heat-treated curable resin composition (a B-stage (semi-cured) optical semiconductor encapsulating resin composition) to obtain the granular curable resin composition.

[0089] The optical semiconductor encapsulating resin composition of the present invention obtained by the above-mentioned production method, when cured by the following method (cylinder shape with size: diameter 50 mm × thickness 1 mm), preferably has a linear transmittance at a wavelength of 400 nm of 50% or more, more preferably 60% or more, even more preferably 70% or more, particularly preferably 80% or more, most preferably 90% or more, and most preferably 95% or more, with no particular upper limit. This makes it possible to more suitably suppress deterioration due to light. (Method of producing hardened body) The resin composition is transferred into a mold heated to 150±5°C under pressure using a transfer molding machine, and the resin is extruded by transfer molding into a mold that has been molten by heating, and cured for 4 minutes without any voids to obtain a uniform cured product. The product is then removed from the mold and heated in a dryer at 150°C for 3 hours to completely cure, obtaining a cured product.

[0090] The resin composition for sealing optical semiconductors of the present invention obtained by the above-mentioned manufacturing method, etc., preferably has a linear transmittance of 50% or more at a wavelength of 400 nm after performing solder reflow three times at 265° C. on a cured product (cylinder-shaped with a diameter of 50 mm and a thickness of 1 mm) obtained by the above-mentioned method, more preferably 60% or more, even more preferably 70% or more, particularly preferably 80% or more, most preferably 90% or more, and most preferably 93% or more, with no particular upper limit. This makes it possible to more suitably suppress deterioration due to light and heat resistance.

[0091] The solder reflow is performed using the cured body in a reflow furnace under conditions of a top peak temperature of 265° C. and 10 seconds per cycle.

[0092] The linear transmittance is determined by measuring the transmission spectrum of the cured product at a wavelength of 400 nm using a spectrophotometer. The transmission spectrum is measured in a direction perpendicular to the bottom surface (or top surface) of the sample.

[0093] In order to prepare a resin composition for sealing an optical semiconductor having the linear transmittance and linear transmittance after three reflow cycles within the above ranges, the composition may be prepared according to the following guidelines. (1) Use of raw materials having an isosorbide structure. This is because the isosorbide structure is an alicyclic structure and therefore has excellent light transmittance, which results in suppression of deterioration due to light and excellent heat resistance. (2) Use a compound with few aromatic rings, such as a bisphenol structure, because aromatic rings absorb light in the short wavelength region and can cause a decrease in heat resistance. (3) Even when a compound having an aromatic ring is used, a compound having no conjugated structure is used. This is because a compound having an aromatic ring and a conjugated structure has high light absorption in the range of 280 nm to 320 nm, whereas a compound having an aromatic ring but no conjugated structure has almost no light absorption in the range of 280 nm to 400 nm. (4) A compound having cyclohexane is used, because the compound having cyclohexane has almost no light absorption in the range of 280 nm to 400 nm.

[0094] The optical semiconductor encapsulating resin composition of the present invention obtained by the above-mentioned production method or the like has a glass transition temperature of preferably 0° C. or higher, more preferably 70 to 200° C., even more preferably 90 to 180° C., and particularly preferably 100 to 160° C., of a cured product (cylinder with dimensions: diameter 50 mm × thickness 1 mm) obtained by the above-mentioned method. This improves resistance to temperature cycle tests and yellowing. In this specification, the glass transition temperature of the cured product is measured by the method described in the Examples.

[0095] The optical semiconductor encapsulating resin composition of the present invention obtained by the above-mentioned production method or the like has a Shore D hardness of a cured product (cylinder shape with dimensions of 50 mm diameter × 1 mm thickness) obtained by the above-mentioned method of preferably 50 to 100, more preferably 60 to 100, and further preferably 70 to 100. This can improve impact resistance. In this specification, the Shore D hardness of the cured product is measured by the method described in the Examples.

[0096] In order to prepare a resin composition for sealing an optical semiconductor having a glass transition temperature and Shore D hardness within the above ranges, the composition may be prepared according to the following guidelines. (1) A material with an alicyclic and rigid chemical structure is used, because this allows the glass transition temperature to be adjusted. (2) A multifunctional alicyclic epoxy material is used, which allows the glass transition temperature to be adjusted.

[0097] The resin composition for sealing optical semiconductors of the present invention obtained by the above-mentioned production method or the like has a spiral flow length of preferably 50 to 350 cm, more preferably 140 to 300 cm, measured according to EMMI (Epoxy Molding Materials Institute) standard 1-66 under conditions of a mold temperature of 150°C, a molding pressure of 970 kgf / cm2, a curing time of 120 s, and an injection speed of 2.0 cm / s. If the spiral flow length is too short, the mold filling property tends to decrease, and if the spiral flow length is too long, there is a risk of leakage from the mold and causing resin burrs.

[0098] The gelation time of the optical semiconductor encapsulating resin composition of the present invention obtained by the above-mentioned manufacturing method or the like, measured according to EMMI (Epoxy Molding Materials Institute) standard 1-66 under conditions of a mold temperature of 150°C, molding pressure of 970 kgf / cm2, curing time of 120 s, and injection speed of 2.0 cm / s, is preferably 10 to 60 seconds, more preferably 20 to 50 seconds. If the gelation time is too short, curing may be too fast, making it difficult to fill the mold, and if the gelation time is too long, curing may be too slow, tending to reduce productivity. In this specification, the spiral flow length and the gelation time are measured by the method described in the Examples.

[0099] In order to prepare a resin composition for sealing an optical semiconductor having the above-mentioned spiral flow length and gel time within the above-mentioned ranges, the composition may be prepared according to the following guidelines. (1) The composition can be adjusted to fall within the above range by subjecting the resin composition to a heat treatment at 40 to 70° C. The lower the temperature at which the composition is treated, the easier it is to adjust the composition.

[0100] The viscosity of the optical semiconductor encapsulating resin composition of the present invention obtained by the above-mentioned production method or the like is preferably 50 to 300 dPa·s, more preferably 80 to 150 dPa·s, thereby ensuring the fillability into a mold. In this specification, the viscosity is measured by the method described in the Examples.

[0101] In order to prepare a resin composition for sealing an optical semiconductor having a viscosity within the above range, the composition may be prepared according to the following guidelines. (1) The composition can be adjusted to fall within the above range by subjecting the resin composition to a heat treatment at 40 to 70° C. The lower the temperature at which the composition is treated, the easier it is to adjust the composition.

[0102] The optical semiconductor encapsulating resin composition of the present invention is suitably used for transfer molding applications.

[0103] <Resin moldings for sealing optical semiconductors> The optical semiconductor encapsulating resin molded product of the present invention may be in the form of a tablet, sheet or the like, and can be molded so as to cover an optical semiconductor element constituting an optical semiconductor device, thereby encapsulating the element.

[0104] When the resin molded product for sealing optical semiconductors is a tablet, its volume is not particularly limited, but is preferably 1 to 100 cm. 3 is preferable, and 10 to 100 cm 3 is more preferred.

[0105] The method for producing a resin molded product for encapsulating an optical semiconductor of the present invention includes, in addition to the above steps, for example, a step of molding the granular resin composition obtained in the step of obtaining the granular curable resin composition.

[0106] The optical semiconductor encapsulating resin composition of the present invention is molded to obtain an optical semiconductor encapsulating resin molded product of the present invention. This results in an optical semiconductor encapsulating resin molded product containing the optical semiconductor encapsulating resin composition of the present invention. Examples of the molded product include tablets and sheets, and molding methods include tableting to obtain tablets and extrusion molding to obtain sheets. The molded product obtained is an environmentally friendly, high-quality molded product.

[0107] The optical semiconductor encapsulating resin composition is molded to obtain an optical semiconductor encapsulating resin molded product, and the optical semiconductor encapsulating resin composition and the optical semiconductor encapsulating resin molded product have substantially the same composition.

[0108] When the molded product is a tablet, the conditions for tablet compression molding are appropriately adjusted depending on the composition of the optical semiconductor encapsulating resin composition, but in general, the compression ratio during tablet compression molding is preferably set to 90 to 96%. That is, if the compression ratio value is less than 90%, the density of the tablet may be low and the tablet may be easily broken, and conversely, if the compression ratio value is more than 96%, cracks may occur during tablet compression, causing chipping or breaking during demolding.

[0109] <Optical semiconductor encapsulation materials, optical semiconductor devices> The optical semiconductor encapsulation molded resin product of the present invention is used to encapsulate an optical semiconductor element by a molding method such as transfer molding to produce an optical semiconductor device. That is, the optical semiconductor encapsulation molded resin product of the present invention becomes an optical semiconductor encapsulant that resin-encapsulates an optical semiconductor element by molding such as transfer molding. In this way, the optical semiconductor encapsulant of the present invention is obtained by molding the optical semiconductor encapsulation molded resin product of the present invention. In this specification, the optical semiconductor encapsulant is a member that is formed so as to cover an optical semiconductor element that constitutes an optical semiconductor device, and encapsulates the element.

[0110] The optical semiconductor encapsulating resin composition and the optical semiconductor encapsulating resin molded product of the present invention are environmentally friendly, and therefore an optical semiconductor encapsulant obtained by molding the optical semiconductor encapsulating resin composition or the optical semiconductor encapsulating resin molded product of the present invention is an environmentally friendly, high-quality optical semiconductor encapsulant.

[0111] The optical semiconductor device of the present invention comprises an optical semiconductor element and the optical semiconductor encapsulant of the present invention that encapsulates the optical semiconductor element. Since the optical semiconductor device of the present invention comprises the optical semiconductor encapsulant of the present invention, it is an environmentally friendly, high-quality optical semiconductor device.

[0112] The optical semiconductor encapsulating resin composition and the optical semiconductor encapsulating resin molded product of the present invention, when cured, have excellent light transmittance, and as a result, can suppress deterioration due to light, and further have excellent heat resistance. Therefore, the resin composition for encapsulating optical semiconductors and the resin molding for encapsulating optical semiconductors of the present invention can be suitably used as an encapsulant for a light-emitting element and an encapsulant for a light-emitting device equipped with a light-emitting element, and can be more suitably used as an encapsulant for a light-emitting diode and an encapsulant for a light-emitting device equipped with a light-emitting diode. Similarly, the optical semiconductor device of the present invention is preferably a light emitting device having a light emitting element, and more preferably a light emitting device having a light emitting diode. Examples of light-emitting elements include UV light-emitting elements such as UV-A (315-400 nm) light-emitting elements, UV-B (280-315 nm) light-emitting elements, and UV-C (100-280 nm) light-emitting elements; and visible light light-emitting elements such as R (red) light-emitting elements, G (green) light-emitting elements, and B (blue) light-emitting elements. The light emitting element is preferably a light emitting diode. The light emitting diode can be of a bullet type, a chip type (surface mount type), etc., but the chip type is preferred, and a chip LED is more preferred. EXAMPLES

[0113] Next, examples will be described together with comparative examples, but the present invention is not limited to the following examples.

[0114] The materials used are shown below. Plant-derived biodiol 1: Benebiol HS0850H manufactured by Mitsubishi Chemical Corporation (polymer represented by the formula (A), in 100% by mass of the polymer, the proportion of structural units derived from isosorbide: 44% by mass, the proportion of structural units derived from 1,6-hexanediol: 56% by mass, number average molecular weight: 800, hydroxyl value: 140 mgKOH / g, bio ratio: 44% by mass (diol using plant-derived isosorbide)) Plant-derived Biodiol 2: BioPTMG650 manufactured by Mitsubishi Chemical Corporation (environmentally friendly polytetramethylene ether glycol made from plant-derived raw materials, number average molecular weight: 650, hydroxyl value: 160-187 mgKOH / g) Petroleum-derived diol 1: ADEKA P-700 (polyethylene glycol) Petroleum-derived diol 2: NPG (neopentyl glycol) manufactured by Mitsubishi Gas Chemical Trading Co., Ltd. Epoxy resin 1: Epokukdo YD-012W (bisphenol A type epoxy resin) manufactured by Kukdo Chemical Co., Ltd. Epoxy resin 2: TEPIC-S (triglycidyl isocyanurate (epoxy equivalent 100)) manufactured by Nissan Chemical Industries, Ltd. Epoxy resin 3: Daicel's EHPE3150 (alicyclic epoxy resin (epoxy equivalent 180)) Hardener 1: Rikacid MH-700G (hexahydrophthalic anhydride) manufactured by New Japan Chemical Co., Ltd. Hardener 2: Rikacid HH (HHPA, hexahydrophthalic anhydride) manufactured by New Japan Chemical Co., Ltd. Antioxidant 1: H-BHT (2,6-di-tert-butyl-p-cresol) manufactured by Honshu Chemical Industry Co., Ltd. Antioxidant 2: HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) manufactured by Sankosha Antioxidant 3: TPP-R (triphenyl phosphite) manufactured by Daihachi Chemical Industry Co., Ltd. Silane coupling agent: Shin-Etsu Silicone's KBM803 (3-mercaptopropyltrimethoxysilane) Curing accelerator 1: N,N-dimethylbenzylamine manufactured by Tokyo Chemical Industry Co., Ltd. Curing accelerator 2: Hishicoline PX4MP (methyltributylphosphonium iodide) manufactured by Nippon Chemical Industry Co., Ltd.

[0115] Examples and Comparative Examples The raw materials were mixed at 100 to 150°C in the amounts shown in Table 1. The curable resin composition obtained by mixing was heat-treated to obtain a B-stage (semi-cured) optical semiconductor encapsulating resin composition. The heating and dissolving temperature, heat treatment temperature, and heat treatment time were appropriately changed depending on the properties of the thermosetting resin.

[0116] The optical semiconductor encapsulating resin compositions prepared in the respective Examples and Comparative Examples were evaluated by the methods described below. The evaluation results are shown in Table 1.

[0117] <Preparation of test piece (hardened body)> The optical semiconductor encapsulation resin composition (resin composition melted by heating) prepared as described above was extruded under pressure into a mold heated to 150±5°C using a transfer molding machine, and cured for 4 minutes without voids to obtain a uniform cured product, thereby producing a test specimen cured product (size: cylindrical with a diameter of 50 mm and a thickness of 1 mm). This was heated at 150°C for 3 hours to complete curing, and a test specimen was obtained.

[0118] <Linear transmittance> First, the quartz cell was filled with liquid paraffin manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and the baseline was measured using a spectrophotometer V-670 manufactured by JASCO Corporation. Then, the test piece (cylinder shape with a diameter of 50 mm and a thickness of 1 mm) prepared as described above was immersed in liquid paraffin in the quartz cell, and the light transmittance (linear transmittance) at a wavelength of 400 nm was measured at room temperature (25°C) using a spectrophotometer (V-670 manufactured by JASCO Corporation) in a state in which light scattering on the sample surface was suppressed. The measurement of the transmission spectrum was performed in the direction perpendicular to the bottom surface of the sample (thickness direction).

[0119] <Glass transition temperature (Tg)> The storage modulus E' and loss modulus E'' of the test piece prepared above were measured using an RSA-II manufactured by RHEOMETRIC SCIENTIFIC under the measurement conditions of tensile mode, frequency 1 Hz, scanning temperature 0 to 270°C, and heating rate 10°C / min. From these, a curve of tan δ (=E'' / E') was obtained, and the peak top temperature of tan δ was calculated.

[0120] <Solder reflow> The test piece prepared above was passed through a reflow furnace (top peak 265°C x 10 seconds) three times. For the test piece after three solder reflows, the linear transmittance (linear transmittance at a wavelength of 400 nm after three solder reflows at 265°C) was measured according to the method described above in <Linear transmittance>. The higher the linear transmittance at a wavelength of 400 nm after three solder reflows at 265°C (the higher the linear transmittance maintenance rate before and after reflow), the more excellent the heat resistance.

[0121] <Shore D hardness> The hardness of the test pieces prepared above was measured at 25° C. using a Shore D hardness tester.

[0122] <Spiral flow length, gelation time> The reactivity of the optical semiconductor encapsulating resin composition prepared above was adjusted at 40 to 80° C., pulverized, and tablet-molded to prepare optical semiconductor encapsulating resin tablets. Spiral flow length and gel time are based on EMMI (Epoxy Molding Materials Institute) standard 1-66, with a mold temperature of 150°C and molding pressure of 970kgf / cm 2 The measurements were performed under the conditions of 120 s curing time and 2.0 cm / s injection speed. Specifically, using a fluidity measuring device, the obtained tablets were coarsely crushed and passed through a sieve with an opening diameter of 5 mm, and the powder was placed in a pod maintained at 150°C, and pressed by pushing the plunger at a constant speed. The spiral flow length was calculated by measuring the amount of plunger displacement and the time it took. The gelation time was measured as the time from the start of the measurement until the plunger speed reached a constant value.

[0123] <Viscosity> The measurements were performed according to EMMI (Epoxy Molding Materials Institute) standard 1-66, under the conditions of a mold temperature of 150°C, molding pressure of 970kgf / cm2, curing time of 120s, and injection speed of 2.0cm / s. Specifically, using a flowability measuring device, the obtained tablets were coarsely crushed, and the powder that had passed through a sieve with an opening diameter of 5mm was placed in a pod maintained at 150°C, and pressed by pushing the plunger at a constant speed. The melt viscosity calculated from the measured torque was plotted against time, and the value b obtained by subtracting the minimum melt viscosity from the index viscosity of 800dPa·s and the time a required for the melt viscosity to reach 800dPa·s again during the curing process after passing through the minimum melt viscosity were calculated.

[0124] <Crushability> A 1 kg weight was dropped from a height of 30 cm onto the optical semiconductor encapsulation resin composition (thickness 5 cm) prepared above, and it was judged whether the composition broke or not. If the composition broke, the crushability was rated as ◯, and if it did not break, the crushability was rated as ×.

[0125] <Tabletability (tabletization)> The resin composition for sealing optical semiconductor prepared above was adjusted in reactivity at 40 to 80°C, pulverized, and molded into tablets to prepare resin tablets for sealing optical semiconductor. The tablets prepared were visually evaluated for cracks and chips. When there were no cracks or chips, the tabletability was evaluated as ◯, and when there were cracks or chips or fusion, the tabletability was evaluated as ×.

[0126] [Table 1]

[0127] From the experimental results shown in Table 1, it was found that the examples using optical semiconductor encapsulating resin compositions having a bio ratio of 10 mass % or more were environmentally friendly and had the properties required for an optical semiconductor encapsulating resin composition. [Industrial Applicability]

[0128] The present invention relates to an optical semiconductor encapsulation resin composition used for encapsulating an optical semiconductor element, and an optical semiconductor encapsulation resin molded product, which can be utilized in the manufacture of an optical semiconductor encapsulant and an optical semiconductor device.

Claims

1. A resin composition for sealing optical semiconductors, having a bio ratio of 10 mass% or more.

2. 2. The optical semiconductor encapsulating resin composition according to claim 1, which contains a diol derived from a plant.

3. 3. The resin composition for sealing an optical semiconductor according to claim 2, wherein the diol has hydroxy groups at both ends of the main chain.

4. 3. The optical semiconductor encapsulating resin composition according to claim 2, wherein the diol is a polymer.

5. 3. The resin composition for sealing optical semiconductors according to claim 1 or 2, which has a linear transmittance of 50% or more at a wavelength of 400 nm when cured into a cylindrical product (size: diameter 50 mm × thickness 1 mm) by the following method. (Method of Producing a Hardened Body) The resin composition is transferred into a mold heated to 150±5°C under pressure using a transfer molding machine, and the resin is extruded by transfer molding into a mold heated to 150±5°C. The resin is cured for 4 minutes without any voids to obtain a uniform cured product. The product is then removed from the mold and heated in a dryer at 150°C for 3 hours to completely cure the product, obtaining a cured product.

6. 3. The resin composition for encapsulating optical semiconductors according to claim 1 or 2, wherein the cured product (cylinder-shaped, size: diameter 50 mm × thickness 1 mm) obtained by the above method has an in-line transmittance of 50% or more at a wavelength of 400 nm after solder reflow is performed three times at 265°C.

7. 3. The resin composition for sealing optical semiconductors according to claim 1, wherein the glass transition temperature of the cured product (cylindrical with dimensions of 50 mm diameter x 1 mm thickness) obtained by the above method is 0°C or higher.

8. 3. The optical semiconductor encapsulating resin composition according to claim 1, which is used for transfer molding.

9. 3. A resin molded article for encapsulating an optical semiconductor, comprising the resin composition for encapsulating an optical semiconductor according to claim 1 or 2.

10. An optical semiconductor encapsulant obtained by molding the optical semiconductor encapsulating resin molded product according to claim 9.

11. An optical semiconductor device comprising: an optical semiconductor element; and the optical semiconductor encapsulant according to claim 10 for encapsulating the optical semiconductor element.

Citation Information

Patent Citations

  • Encapsulating resin composition for surface-mounted discrete devices in LED displays and its uses

    JP2021528503A